B2B e-commerce adoption among small & medium enterprises : An analysis of multinomial logit model - Thi, Lip Sam; Lim, Hock Eam; Ang, Chooi Leng (2010)

(untitled)
This paper examines the factors that influence e-commerce adoption levels among SMEs in Malaysia. Based on Technological-Organisational-External(T0) framework, it is found that external support is significant across all e-commerce adoption levels. This finding suggests that future policy to encourage e-commerce uptake in Malaysia should focus on providing support to facilitate e-commerce adoption effort. The findings also show that owners or CEOs of SMEs who are more experienced, have completed tertiary education and used computer frequently, are more likely to adopt e-commerce. Hence, to further promote e-commerce adoption among SMEs,owners or CEOs of SMEs who are less experienced, high-school leavers, and who used computer less frequently, ought to be targeted in future e-commerce initiatives. Relatively, based on TOE framework, CEO attributes are more significant in terms of e-commerce adoption among SMEs in Malaysia.